Cordia africana but not Juniperus procera and Podocarpus falcatus respond positively to arbuscular mycorrhizal fungi at the early stages of seedling development - Fisseha Asmelash; Tamrat Bekele; Zerihun Belay; Fassil Kebede (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Asmelash F, Bekele T, Belay Z, Kebede F. 2021. Cordia africana but not Juniperus procera and Podocarpus falcatus respond positively to arbuscular mycorrhizal fungi at the early stages of seedling development. Biodiversitas 22: 2971-2980. AMF (Arbuscular mycorrhizal fungi) inoculation could be an important technology to improve the growth and field survival of trees. Hence, we evaluated the mycorrhizal responsiveness of Cordia africana Lam., Juniperus procera (Hoechst. ex Endl.), and Podocarpus falcatus (Thumb.) Mirb. seedlings. Seedlings germinated on sterile sand were transplanted to 1-liter plastic pots filled with sterile and non-sterile degraded bulk soil. Rhizospheric soil from adult C. africana and J. procera were used as whole-soil AMF inocula. Cordia africana and J. procera received conspecific whole-soil AMF inocula while P. falcatus received J. procera inoculum. Hence, in the two-by-two factorial experiment, we also evaluated the growth effects of AMF inoculation, soil type, and their interaction. On the sterile potting soil, MRi (mycorrhizal responsiveness due to AMF inoculation) of C. africana was positive and significantly (p<0.05) greater than the MRi of J. procera and P. falcatus. However, on the non-sterile potting soil, it was significantly greater than the MRi of P. falcatus only. MRs (MR due to the existing potting soil inocula) and considering all growth variables were mostly positive for C. africana but negative for J. procera and P. falcatus. AMF inoculation significantly increased most growth variables of C. africana seedlings and no significant “inoculation” x “soil type” interaction effects were detected. Hence, AMF inoculation of C. africana seedlings could be merited and under wide range of field conditions. In the case of J. procera and P. falcatus, after-planting care could be more appropriate